(untitled) (Journal of the College of Basic Education, 2026)
The research aims to reveal the differences in a number of variables among students of private universities (Jihan, Knowledge, Lebanese-French), namely: the level of intellectual security, university components (faculty, student, university administration, university building, educational content), and the level of independent behavior, in addition to knowing the differences in these variables according to the gender variable (male - female), as well as analyzing the correlational relationship between intellectual security, university components, and independent behavior. The research relied on the descriptive correlational approach, and the sample consisted of (500) male and female students from the three universities, distributed as follows: (150) from Knowledge University, (175) from Jihan, and (175) from Lebanese-French. To achieve the research objectives, three scales were constructed: intellectual security (23 items with five-point options), university components (27 items in five areas), and independent behavior (15 items with four-point options). The validity and reliability of the instruments were verified, and the data were analyzed using SPSS. The results showed no significant differences in intellectual security by university or gender. However, differences appeared in favor of Knowledge University across all university components, with the exception of independent behavior, which favored Cihan University and the Lebanese-French University. Differences also appeared in educational content favoring females. Finally, the results revealed a positive correlation between intellectual security, university components, and independent behavior. The study concluded with a number of recommendations and proposals.